A kaleidoscopic survey of Jayakanthan's prefaces to his short stories - Hemalatha, S. (Chennai Today Publication, 2005)
History of Kashmiri Pandits and Kashmir, India.
Includes bibliographical references
Keywords: Jayakanthan, 1934- -- Criticism and interpretation